Nutlin-Induced Apoptosis Is Specified by a Translation Program Regulated by PCBP2 and DHX30 - Rizzotto, Dario (Cell Rep, 2020)
Activation of p53 by the small molecule Nutlin can result in a combination of cell cycle arrest and apoptosis. The relative strength of these events is difficult to predict by classical gene expression analysis, leaving uncertainty as to the therapeutic benefits. In this study, we report a translational control mechanism shaping p53-dependent apoptosis. Using polysome profiling, we establish Nutlin-induced apoptosis to associate with the enhanced translation of mRNAs carrying multiple copies of an identified 3′ UTR CG-rich motif mediating p53-dependent death (CGPD-motif). We identify PCBP2 and DHX30 as CGPD-motif interactors. We find that in cells undergoing persistent cell cycle arrest in response to Nutlin, CGPD-motif mRNAs are repressed by the PCBP2-dependent binding of DHX30 to the motif. Upon DHX30 depletion in these cells, the translation of CGPD-motif mRNAs increases, and the response to Nutlin shifts toward apoptosis. Instead, DHX30 inducible overexpression in SJSA1 cells leads to decreased translation of CGPD-motif mRNAs.